The shapley value for carbon allocation problem - Md. Ngadiran, Nuraliyah Sallehah (2010)
Free Space Optics (FSO) is a promising optical technology that has a great chance to compliment the traditional wireless communication in the future. Nowadays, it used for last mile solution of metro network, within campus and for military system. The advantages of FSO are it offers the abundance of unregulated bandwidth, high data rate, security, and lower cost for equipment and deployment. The main constrain in FSO transmission channel is attenuation caused by several of weather conditions such as rain and haze conditions that cause the degradation of performance signal. This paper is about the comparison of haze attenuations in FSO between September 1997 and September 2007 at Petaling Jaya region. The largescale air qualify disaster occur that effect widespread atmosphere visibility due to fires in Kalimantan forest is the reason on choosing haze effect on September 1997. This paper also compared between the distance of FSO transmission for 300m and 500m distance in rain condition. The data for visibility for both years are obtained from Malaysia Metrological Department (MMD) while the data of rain intensity is obtained from previous student This project uses LED as a transmitter and PIN photodiode as a receiver with wavelength 1310nm where considered for short distance transmission of 300m and 500m. The results were found to be satisfactory. For haze condition, FSO transmission on September 1997 produces the worse signal performance than transmission on September 2007. For rain condition, the FSO transmission for 300m distance produce the better quality signal than transmission for 500m distance where at 500m distance, the BER value is 10’2 which produce the bad quality signal at receiver. It is hoped with the data available for various atmospheric conditions will help in the implementation of FSO system in Malaysia in the future.